Assets-based approaches to developing age friendly communities: learning from the bristol ageing better programme. Issue 1 (13th October 2021) - Beardmore, Amy; Beynon, Penny; Crabbe, Christine; Fry, Carol; Fullforth, Jan; Groome, Jeremy; Knasel, Eddy; Turner, Jill; Orlik, Christopher; Jones, Matthew; White, Jo
Abstract : Purpose: International attention is increasingly turning to the challenge of creating age-friendly environments. This study aims to examine the application of asset-based approaches in undertaking community development projects with older people. The paper intends to share the learning that may be useful when designing community development projects for older people in the future. Design/methodology/approach: This study followed a multiple project case study design, with a focus on project delivery practices. It was undertaken as a co-production exercise involving university researchers and trained older volunteer community researchers (CRs). Over 18–24 months of qualitative research was conducted in relation to six area-based urban projects between 2018 and 2020. Findings: There were five leading themes as follows: mapping and building on assets in highly localised settings; creating governance and direction through steering groups; developing activities with diverse groups of older people; reaching isolated and lonely older people; building local capacity to embed sustainability. Practical implications: The effectiveness of assets-based approaches in promoting age-friendly agendas appears to be contingent on the values, skills, capacity and resourcing of delivery agencies, alongside wider public sector investment in communities. Diversity and inequalities amongst older people need to be taken into account and community development that specifically focuses on older people needs to be balanced with the whole population and intergenerational practice. Originality/value: This paper provides an empirical account of the practical application of assets practices specifically in the context of the age-friendly community agenda. The co-production method brings together insights from academic and volunteer older CRs.